ADSORPTION OF GOLD FROM AQUEOUS SYSTEMS USING MICROBIAL THERMOPHILIC PROTEINS - Kasmiarno, Laksmi Dewi; Chang, Jo Shu (ITB Journal Publisher, LPPM ITB, 2020)
A precious metal such as gold can be obtained from mining. Metals in low concentrations at geothermal sites or in industrial waste are difficult to gain using the conventional mining process. Alternative approaches for recovering metals from dilute solutions have been developed, such as biosorption, i.e. adsorption using microorganisms or their derivatives. In this study, gold in an aqueous system was recovered via biosorption using proteins produced from an isolated thermophilic bacterial strain. Modified Thermus enhanced medium was used as the medium to improve protein production from the thermophilic bacterial strain. The microbial proteins showed effective conditions for Au3+ ion adsorption. The optimum adsorption conditions for Au ions occurred at pH 1 with an adsorption capacity of 482.0 mg/g protein. The metal ion adsorption capacity increased with increasing temperature. The adsorption isotherm was conducted at room temperature, because the Au ions could be well fitted by the Freundlich isotherm equation with qmax at 527.229 mg/g protein.